Analisis Kevalidan Modul IPA Berbasis Problem Based Learning - Lovisia, Endang; Febrianti, Yuli (Science and Physics Education Journal (SPEJ, 2023)
Abstract: This research aims to 1) Design a Problem Based Learning based science module 2) Measure the feasibility of a Problem Based Learning based science module in terms of validity, practicality and effectiveness. The method used is a research and development approach which is usually known as the R&D research method. The development design used is a 4D model development design. The research results show that from the analysis of the three validators, namely material, media and language experts, they obtained a value of 0.89, which is in the very valid category. Key word: Analysis, Science Module, Problem Based Learning